The role of the national university in developing nations’ digital cultural heritage projects - Dowding, Heidi (OCLC Systems & Services. Emerald Group Publishing Limited, 2014)
Purpose – The purpose of this paper is to explore the role of the national university in developing sustainable cultural heritage digital preservation practices. Design/methodology/approach – Using Nazarbayev University in Astana, Kazakhstan as an example, this paper discusses current development of cultural heritage digital collections, and looks to the university library’s impact on nationwide digital practices development. Findings – While the university and its digital collections are still nascent, NU will likely have a large impact on the creation of sustainable digital cultural heritage preservation practices due to its international visibility and direct connection to stakeholders. Originality/value – Focused on developing nations, this paper will be of special interest to librarians working in countries facing similar challenges, such as other CIS nations.
A perspective from Kazakhstan
Keywords: digitization; preservation; cultural heritage; digital collections; developing nations; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science